Profiling Human Coronavirus Genomic Data Obtained from Patients in Belarus - M. V. Sprindzuk; A. S. Vladyko; L. P. Titov; V. I. Bernik (Цифровая трансформация)
The new coronavirus infection has caused the death and injury of millions of people and animals. The pandemic has shown the shortcomings of the health care systems of even the most economically developed countries. Genomics and bioinformatics provide an opportunity to obtain, study and analyze the genomic texts of microbes, coronaviruses in particular. The article presents the results of the analysis of SARS-CoV-2 genomes from patients in Belarus and (for comparison) in Russia. Genomic profiling was performed to identify and statistically analyze clusters and lines of transmission of the new coronavirus infection, in accordance with the proposed classifications of COVID-19 clades. The information on the assessment of the quality of the initial data are reported, the visualization of the results obtained is made and graphically presented. The dominant clades-clusters in Belarus and Russia are B.1 (“Basel cluster”) and B.1.1. Both have European-British geographical distribution